The Influence of Promotion, Service Quality, and Electronic Word of Mouth on Customer Loyalty through Customer Satisfaction on the Instagram Account @rooftopin.nesia - Fauzan, Muhammad Fairuz; Wedhasmara, Ari; Tania, Ken Ditha; Putra, Apriansyah (Sistemasi: Jurnal Sistem Informasi, 2025)
The use of social media has become a key strategy in business development in the era of information technology. Rooftopin Café utilizes social media to build relationships with customers; however, its impact on customer loyalty remains uncertain. This study aims to analyze the influence of promotion, service quality, and electronic word of mouth (e-WOM) on customer loyalty, with customer satisfaction as a mediating variable. Using a quantitative approach, data were collected from 120 respondents—customers who have visited Rooftopin Café in Palembang and follow the Instagram account @rooftopin.nesia. The data were analyzed using SmartPLS. The results show that promotion, service quality, and e-WOM have a positive and significant effect on customer satisfaction. Furthermore, customer satisfaction has a positive and significant influence on customer loyalty. In addition, customer satisfaction is proven to mediate the relationship between service quality and customer loyalty, indicating complementary mediation. This implies that service quality affects customer loyalty not only directly but also indirectly through customer satisfaction.